Flowers for the sea - Rocklyn, Zin E. (TorDotCom, 2021)
"Survivors from a flooded kingdom struggle alone on an ark. Resources are scant, and ravenous sea beasts circle. Their fangs are sharp. Among the refugees is Iraxi: ostracized, despised, and a commoner who refused a prince, she's pregnant with a child who might be more than human, Her fate may be darker and more powerful than she can imagine."--Page 4 of cover.